Model Pembiayaan Pendidikan Islam Berlapis Melalui Integrasi ZIS dan Wakaf Produktif - Fadhli Arsil; Ahmad Suryadi; Kosasih Ali Abu Bakar; Nasuhi Nasuhi (Ikatan Da'i Indonesia, 2026)
This study aims to reconstruct a sustainable financing model for Islamic educational institutions through the integration of zakat, infaq, sadaqah, and productive waqf. This study is motivated by limited educational financing, Islamic educational institutions’ dependence on routine funding sources, and the substantial potential of ZIS and waqf that has not yet been fully managed in a productive and strategic manner. The study employed a Systematic Integrative Literature Review approach by examining peer-reviewed journal articles published between 2020 and 2026, along with contextual sources from official institutions. The analysis was conducted through descriptive mapping, thematic synthesis, and conceptual model reconstruction. The findings reveal that ZIS and waqf possess different characteristics, functions, and financing horizons, yet they can be strategically integrated without combining their respective contracts and designated purposes. ZIS primarily serves as protective financing to expand educational access and safeguard vulnerable students, while productive waqf functions to establish long-term financing sources through assets, endowment funds, business units, and Sharia-compliant investments. This study proposes a Layered Islamic Education Financing Model consisting of protective financing, developmental financing, and productive financing. These three layers are supported by Sharia compliance, professionalism, transparency, accountability, digitalization, risk management, stakeholder collaboration, and impact measurement. The findings affirm that the financial independence of Islamic educational institutions is determined not merely by the amount of available funding, but also by an integrated, productive, and strategically governed financing system oriented toward educational access, quality, and institutional sustainability.